Cytokines of the IL-1 family: recognized targets in chronic inflammation underrated in organ transplantations - Striz, Ilja (Clinical science (London, England, 2017)
Interleukin 1 (IL-1) family is a group of cytokines with multiple local and systemic effects, which regulates both innate and adaptive immune responses. Generally, most IL-1 family cytokines express prevailing pro-inflammatory activities (IL-1α, IL-1β, IL-18, IL-33, IL-36 α, β, γ), whereas others are anti-inflammatory (IL-1Ra (IL-1 receptor antagonist), IL-36Ra, IL-38, IL-37). In addition to their immunomodulatory roles, some of them are also involved in the physiological modulation of homeostatic processes and directly affect mRNA transcription. IL-1 family cytokines bind to specific receptors composed of a ligand-binding chain and an accessory chain. The pro-inflammatory effects of IL-1 family cytokines are regulated on the level of transcription, enzymatic processing of precursors, release of soluble antagonists, and expression of decoy receptors. Members of the IL-1 family regulate the recruitment and activation of effector cells involved in innate and adaptive immunity, but they are also involved in the pathogenesis of chronic disorders, including inflammatory bowel disease, rheumatoid arthritis, and various autoimmune and autoinflammatory diseases. There are only limited data regarding the role of IL-1 cytokines in transplantation. In recent years, targeted therapeutics affecting IL-1 have been used in multiple clinical studies. In addition to the recombinant IL-1Ra, anakinra (highly effective in autoinflammatory diseases and tested for other chronic diseases), the monoclonal antibodies canakinumab, gevokizumab, and rilonacept (a long-acting IL-1 receptor fusion protein) provide further options to block IL-1 activity. Furthermore, new inhibitors of IL-18 (GSK 1070806, ABT-325, rIL-18BP (IL-18 binding protein)) and IL-33 (CNTO-7160) are presently under clinical studies and other molecules are being developed to target IL-1 family cytokines.
Keywords: Animals; interleukin-1; zánět; multigenová rodina; IL-1 family; lidé; transplantační imunologie; Inflammation; Humans; Transplantation Immunology; biologic therapy; cytokines; inflammation; Organ Transplantation; zvířata; Interleukin-1; transplantation; transplantace orgánů; Multigene Family